2017
DOI: 10.1038/srep40847
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the miR-200c/LIN28B axis in acquired EGFR-TKI resistance non-small cell lung cancer cells harboring EMT features

Abstract: MicroRNA (miR)-200 family members (miR-200s) are frequently silenced in advanced cancer and have been implicated in the process of epithelial-to-mesenchymal transition (EMT). We previously reported that miR-200s were silenced through promoter methylation in acquired EGFR-tyrosine kinase inhibitor (TKI) resistant non-small cell lung cancer (NSCLC) cells harboring EMT features. In this study, we examined the functional role of miR-200s in NSCLC cells and investigated a novel approach to overcoming acquired EGFR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 45 publications
3
47
0
Order By: Relevance
“…Thus, activation of the MEK/ERK and PI3K/AKT pathways plays a crucial role in the induction of the EMT phenotype in cancer cells, and our results suggest the possibility that simultaneous inhibition of these two pathways could be effective to overcome the drug resistance caused by the induction of EMT. We previously reported that the expression level of miR‐200c is negatively correlated with EMT features in NSCLC cells with acquired TKI resistance through the reciprocally linked feedback loop with ZEB1 and ZEB2 . Therefore, the conversion from EMT to MET was considered due to the involvement of the negative feedback loop of ZEB1 and miR‐200c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, activation of the MEK/ERK and PI3K/AKT pathways plays a crucial role in the induction of the EMT phenotype in cancer cells, and our results suggest the possibility that simultaneous inhibition of these two pathways could be effective to overcome the drug resistance caused by the induction of EMT. We previously reported that the expression level of miR‐200c is negatively correlated with EMT features in NSCLC cells with acquired TKI resistance through the reciprocally linked feedback loop with ZEB1 and ZEB2 . Therefore, the conversion from EMT to MET was considered due to the involvement of the negative feedback loop of ZEB1 and miR‐200c.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the expression level of miR-200c is negatively correlated with EMT features in NSCLC cells with acquired TKI resistance through the reciprocally linked feedback loop with ZEB1 and ZEB2. 7,44 Therefore, the conversion from EMT to MET was considered due to the involvement of the negative feedback loop of ZEB1 and miR-200c.…”
Section: Discussionmentioning
confidence: 99%
“…36 As a candidate mechanism of drug resistance, EMT plays a crucial role in acquired EGFR-TKIs resistance as reported by different research groups. 37,38 It has been demonstrated that EMT could be regarded as a predictor of therapy response in patients with NSCLC. Furthermore, there is a direct connection between EMT and EGFR-TKIs sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…During EMT, the PRC2 complex is recruited to the CDH1 promoter by the EMT-TF SNAI1, whereby it catalyzes the trimethylation of histone H3K27 to repress E-cadherin expression (Herranz et al, 2008). The same complex is also responsible for the trimethylation and silencing of miR-200, which gives rise to chemoresistance (Ceppi et al, 2010;Lim et al, 2013;Sato et al, 2017;Tryndyak et al, 2010). PRC1 components, such as BMI1, are considered stem cell factors that support normal stem cells and their transformed counterparts (Park et al, 2004;Valk-Lingbeek et al, 2004).…”
Section: Emt Epigenetics and Chemoresistancementioning
confidence: 99%
“…However, various components of the NuRD complex, and specifically the HDACs, will confer drug resistance to cancer cells (Fu et al, 2011;Li et al, 2014;Sakamoto et al, 2016). Consequently, HDAC inhibitors such as vorinostat, mocetinostat, and valproic acid are currently being evaluated as anti-EMT agents (Bruzzese et al, 2011;Caponigro et al, 2016;Lan et al, 2016;Meidhof et al, 2015;Sakamoto et al, 2016;Schech et al, 2015;Schobert and Biersack, 2017).…”
Section: Emt Epigenetics and Chemoresistancementioning
confidence: 99%